Management Plan under the Joint forest Management - Mukherji, S. D. (Indian Forester, 1994)
Activities of forestry should be planned and executed, keeping the interest of the people and their participation as major thrust on the foreet management. Therefore, the preparation of Management for the Vans samrakahan samiti (VSS) should be more in detail.